Chlamydial antigens stabilized with formalin for use in the micro-immunofluorescence test. - Hanna, L (1980)
Formalinized antigen suspensions prepared by differential centrifugation from crude infected yolk sacs and stored at 4 degrees C were satisfactory antigens during at least 36 weeks when used in chlamydial micro-immunofluorescence procedures.